PENGENDALIAN KECEPATAN MOTOR DC MENGGUNAKAN SENSOR ENCODER DENGAN KENDALI PI - Jumiyatun Jumiyatun (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
Digital control system PI based on microcontroller AT 89S52 is made to control the speed of DC motor. Users can interact via keypad and LCD panel. This control system limits the positive control signal (saturation). The digital PI is a process of a program executed by using a computer, by entering a set point value (SP) then the data will be processed using a predefined PI setting, until the corresponding procces variable (PV) is obtained so that the error is equal to 0, or Set point value = Process variable. Steady state errors that occur due to the restriction (saturation) by using a quarter-second sampling time.